A Survey Research: Happiness Levels and Coping Behaviors with Work-Related Problems among Personnel at Sisaket Rajabhat University - sutawan, chanrapas (Medical Journal of Sakon Nakhon Hospital, 2024)
This survey research aimed to study the happiness levels, coping behaviors with work-related problems, and the relationships between demographic characteristics, happiness, and coping behaviors among personnel at Sisaket Rajabhat University from July 1st to September 30th, 2023. The sample consisted of 138 personnel selected through simple random sampling. The research instruments included the HAPPINOMETER assessment and a work-related coping behavior questionnaire. Data were analyzed using percentage, mean, Chi-square, and Fisher’s exact test. The research results revealed that the level of happiness at work was high at 56.5%. Dimensions 1-7, which include good health, relaxation, kindness, spirituality, family, society, and pursuit of knowledge, were all at high levels. Dimensions 8-9, covering financial health and work satisfaction, were at moderate levels. The overall average happiness level was high ( = 3.47, S.D. = 0.51). Regarding problem-focused coping behaviors at work, the top two practices at high levels were learning from past experiences for self-development and resolving situations based on experience. The overall implementation was at a moderate level ( = 1.88, S.D. = 0.57). For emotion-focused coping behaviors, the top two practices at high levels were increasing activities such as listening to music, playing sports, gardening, and getting more sleep. The overall implementation was at a moderate level ( = 1.55, S.D. = 0.52).